Reusable grid computing architecture based on code propagation method. (9th February 2009) - Krol, Dariusz; Kukla, Grzegorz
In this paper we examine the benefits and limitations of reusable grid computing structure. The key feature of this structure is the ability to hold and manage multiple distributed projects at the same time in the same physical network. We define essential requirements that a grid structure has to meet to be considered reusable. The problems resulting from established assumptions are enumerated. The existing grid computing solutions are analysed from a view of reusability. The design and implementation of reusable grid computing system relying on code propagation methods is discussed in details. The results of experimental verification of theoretical assumptions are included. We show that our choice of building reusable grid framework (RGF) could be successfully applied.